Infusing Digital Literacy in Authentic Academic Digital Practices of English Language Teaching at Universities - Iskandar, Ifan; Sumarni, Sri; Dewanti, Ratna; Asnur, Muhammad Nur Ashar (International Journal of Language Education, 2022)
Digital literacy is a critical element of multiliteracy framework required to thrive in digital era and perceived as cross-curricular competencies, yet it is not adequately addressed in English language teaching. This paper explores the traits of the authentic academic digital practices in the course outlines of English language skills conducive for digital literacy development, examines the extent to which digital literacy are infused in the authentic academic digital practices of the English courses and proposes the procedure of infusing digital literacy in the authentic academic digital practices of English language teaching. The study employs content analysis to address the data—the traits of authentic academic digital practices in fifty-five course outlines of English language skills subjects from six English Language Education and English Literature Study Programs in Jakarta and West Java. The findings recognize the traits of authentic academic digital practices in the digital academic products, such as the answers to open-/closed-ended questions, essays, presentation slides, papers, videos, podcasts, recorded audio-visual presentations, and reports diversely used across the courses. These digital academic products are used merely as the media in which English is used; only English proficiency is highlighted. The underpinning digital competencies to create the media, the media creation process and the media as digital academic products are not sufficiently addressed and measured. Digital literacy is infused in the authentic academic digital practices of English language teaching through five stages of identifying the components of digital literacies and the authentic academic digital practices and products, analysing the descriptors of digital literacies components pertaining to authentic academic digital practices and products, integrating the descriptors of digital literacies into learning outcomes, embedding digital literacies into academic products, employing authentic academic digital practices in the learning process, and assessing digital literacies as cross-curricular competencies